Saint Vincent and the Grenadines. Significant achievements 2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The main activities carried out by the Institute in Saint Vincent and the Grenadines during 2017 are identified, with respect to the needs and interests of the country, strengthening issues such as beekeeping, sustainability, fishing, governance, family farming, perma-beekeeping, through of the use of Perone Hive technology and in resilience against climate change. Likewise, work was done to improve the coffee value chain and the use of ferrocement tanks, for the use of rainwater for irrigation. Finally, support was given to the inclusion of women in agricultural issues and to combat drug theft.